SHORT REFLECTIONS REGARDING PRECAUTIONARY AND PREVENTIVE MEASURES ORDERED IN THE CRIMINAL TRIAL AGAINST AN INSOLVENT LEGAL PERSON - Luminița CRISTIU-NINU (Challenges of the Knowledge Society)
The judicial realities have shown us that the field of the precautionary and preventive measures ruled in the criminal trial against the insolvent judicial person is not correctly and efficiently regulated. There are a series of peculiarities that should be attentively analyzed in order to eliminate the negative effects of the interference of the criminal procedures with those of insolvency. The lack of a specific package of standards that help managing such a situation, but also, sometimes, the misinterpretation of the existing regulations in the field may generate situations that go almost beyond the legal persons in such a position.